Hay ho, hay hum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Silage making in the tropics with particular emphasis on smallholders FAO Plant Production and Protection Papers 161, 2000. 192 pp. ISBN 9251045003 US$ 16 Euro 18.25